Exploring critical components of an integrated STEM curriculum: an application of the innovation implementation framework - Jessica Gale; Meltem Alemdar; Jeremy Lingle; Sunni Newton (SpringerOpen, 2020)
Abstract Background Increased emphasis on accountability in education reform and evidence-based practices underscores the need for research on the implementation of K-12 curricular innovations. However, detailed accounts of research examining fidelity of implementation for K-12 STEM curricula remain relatively scarce. This paper illustrates the application of one frequently cited framework for exploring fidelity of implementation, the innovation implementation framework. The paper describes how this framework was applied to identify and describe the implementation of critical components of a newly developed middle school STEM curriculum. Results Drawing on classroom observations, student interviews, and teacher interviews, the paper provides illustrative findings and practical examples of methodology and instruments employed over the course of a 2-year study of curriculum implementation. The paper discusses three ways in which the innovation implementation framework enhanced our understanding of curriculum implementation: specifying critical components of the curriculum and their enactment, informing instrument design and data collection, and revealing implementation patterns. Conclusions This paper provides support for the use of the innovation implementation framework to study the implementation of curricula developed within the context of research-practice partnerships. In addition to illustrating the application of the innovation implementation framework, the paper extends previous implementation work focused on efficacy and effectiveness studies to demonstrate the practical advantages of studying fidelity of implementation in the context of design and development projects.